Aplicación de interfaces educativas mediadas por TIC: impacto en la efectividad del aprendizaje del sistema de ecuaciones lineales. - Caiza Robalino, Patricio (2025)
Nowadays, where technology advances rapidly and the academic aspect at the high school level presents difficulties in the teaching-learning process, with students who are aware of digital devices and disinterested in traditional classes and teachers concerned about this problem exposed, the work “Application of educational interfaces mediated by ICTs: impact on the effectiveness of learning the system of linear equations” is presented, which has the general objective: to implement educational interfaces mediated by ICT to improve the effectiveness of learning in solving systems of equations. linear. Thus, promoting the development of technological and didactic skills of the second-year students at the unified general high school of the Isabel de Godin Educational Unit. The methodology used in the research has a mixed qualitative-quantitative approach, with the application of an observation sheet and a survey. The qualitative data are presented in statistical tables and graphs with the analysis, and to validate the pedagogical proposal, the t-Student statistic is used between the traditional education model and the virtual education model based on the use of gamification educational interfaces in virtual environments. After the application of the proposal, the results showed that active student participation, both individually and in groups, was achieved in the interactive activities. It was concluded that educational activities mediated by ICT improved the effectiveness of learning in solving systems of linear equations, achieving the development of technological and didactic skills of the students.